Neutrophil Extracellular Traps in Systemic Lupus Erythematosus Stimulate IgG2 Production From B Lymphocytes - Bertelli, Roberta; Schena, Francesca; Antonini, Francesca; Reverberi, Daniele; Signa, Sara; Pedemonte, Nicoletta; Consolaro, Alessandro; Gattorno, Marco; Negrini, Simone; Pupo, Francesca; Volpi, Stefano; Ghiggeri, Gian Marco (Frontiers in Medicine, 2021)
Circulating autoantibodies of IgG2 isotype predominate in Systemic Lupus Erythematosus (SLE) and concur to the development of the renal lesions characteristic of Lupus Nephritis (LN). Anti-dsDNA and anti-histones IgG2, together with anti-podocyte proteins (i.e. α-enolase) are the major autoantibodies, in both serum and renal glomeruli of LN patients. The mechanisms underlying autoantibody formation and isotype switching in SLE and LN are unknown. A major issue is how DNA/histones are externalized from cell nucleus, driving the autoimmune response. Neutrophil Extracellular Traps (NETs) have been recently identified as crucial players in this context, representing the main source of DNA and nucleosome proteins. A second key point is what regulates IgG2 isotype switching: in mouse models, T-bet transcription factor has been described as essential for IgG2a class switch. We hypothesized that, in SLE, NET formation is the key mechanism responsible for externalization of autoantigens (i.e. dsDNA, histones 2,3, and α-enolase) and that T-bet is upregulated and drives immunoglobulin class switch recombination (CSR), with production of IgG2 autoantibodies. Our data show that NETs, purified from SLE patients, stimulate ex vivo IgG2 isotype class switch through the induction of T-bet. Interestingly, we observed a prominent effect of NETs on the release of soluble IgG2 in naïve B cells of SLE patients, but not of healthy donors. Our results add important knowledge for understanding how NETs contribute to LN pathogenesis.